3PC-071 Fully automated central intravenous additive service (CIVAS): a 12 month analysis of performances and impact of COVID-19 on sterile antibiotic production. (14th March 2021) - Vagnoni, F; Leoni, S; Guglielmi, S; Marinozzi, A; Capone, C; Mura, F; Lattanzi, M; Cortese, C; Buccolini, M; Ragnini, M; Pompilio, A
Abstract : Background and importance: In 2014, the hospital pharmacy started a project to implement a central intravenous additive service (CIVAS) unit. A pre-feasibility study was performed, a new class C clean room equipped with the robotic system APOTECA unit was built and the fully automated aseptic production process was validated. In 2016, the CIVAS started producing standard doses of chemotherapy supportive treatments (palonosetron, ondansetron, dexamethasone) in ready-to-administer form for the oncology and haematology units. The production was then shifted to antibiotics (cefazolin, piperacillin–tazobactam, ceftriaxone) and pantoprazole for infectious disease, cardiac surgery and emergency medicine departments. Currently, the in-advance production of batch preparations at CIVAS is mainly based on daily consumption and performed by one pharmacy technician and one pharmacist (0.25 full time equivalent each). The working day is from 8am to 4pm (Monday–Friday). Aim and objectives: The aim of this study was to analyse the performance of the CIVAS over the past year and evaluate the impact of the COVID-19 pandemic on the increasing demands for sterile antibiotics by emergency departments. Material and methods: Overall CIVAS production, dosage accuracy and average production time (APT) of each ready-to-administer preparation were evaluated over a period of 12 months (from September 2019 to August 2020). Data were collected from the APOTECA statistical tool. Results: 12 215 preparations were compounded, of which 26% were in syringe (1 g cefazolin, APT 125 s) and 74% in 100 mL NaCl 0.9% infusion bags (55% for 4.5 g piperacillin–tazobactam, ATP 203 s; 14% for 40 mg pantoprazole, ATP 196 s; 5% for 2 g ceftriaxone, ATP 177 s). Average dosage accuracy for all preparations was 98.9±1%. During the peak of Italy's COVID-19 outbreak (March 2020), weekly production increased by 28%. The production of pantoprazole remained steady, while piperacillin–tazobactam and ceftriaxone for the emergency departments increased considerably (+19% and 9%, respectively) and cefazolin for the cardiac surgery department decreased by 26%. Conclusion and relevance: Implementation of a fully automated CIVAS allows measuring and controlling every step of the production process for ready-to-administer preparations. The study showed that CIVAS met increasing demands for sterile antibiotics during the pandemic crisis, thereby supporting the emergency units and providing the highest level of quality and safety. References and/or acknowledgements: Bufarini C. Centralised non-hazardous intravenous compounding: improvement of clinical practice. Eur J Hosp Pharm 2018. Conflict of interest: No conflict of interest